Variations in Presentation and Management of COVID-19 Inpatients by Race and Ethnicity in a Large Texas Metroplex. (12th July 2023) - Liu, Alison; Patel, Akshat; Pierce, Ava; Fowler, Ray
Abstract: Objective: The aim of this study was to assess variations in presentation and outcomes of coronavirus disease 2019 (COVID-19) across race/ethnicity at a large Texas metroplex hospital. Methods: A retrospective cohort study was performed. Results: Although COVID-19 patients demonstrated significant socioeconomic disparities, race/ethnicity was not a significant predictor of intensive care unit (ICU) admission ( P = 0.067) or case fatality ( P = 0.078). Hospital admission varied by month, with incidence among Black/African-American and Hispanic/Latino patients peaking earlier in the pandemic timeline ( P < 0.001). Patients reporting Spanish as their primary language were significantly more likely to be admitted to the ICU (odds ratio, 1.75; P = 0.007). Conclusions: COVID-19 patients do not demonstrate significant racial/ethnic disparities in case fatality, suggesting that state-wide disparities in mortality rate are rooted in infection risk rather than hospital course. Variations in admission rates by race/ethnicity across the timeline and increased ICU admission among Spanish-speaking patients demonstrate the need to pursue tailored interventions on both a community and structural level to mitigate further health disparities throughout the pandemic and after.